2015
DOI: 10.1007/s00231-015-1660-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boundary conditions on thermal plume growth

Abstract: The advent of a verifiable theory allowed experimentalists to start measuring the proportionality coefficient. However, estimates of the coupling coefficient were quite different due to some reasons. First of all, laboratory setups differed in design. Difference in the nature of working fluids or in heating techniques (e.g., in dimensions and shape of measuring cells) led researchers to repeatedly differing results. Therefore, while comparing experimental results, a necessity to ascertain the influence of boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…According to previous studies (Moses et al 1993;Kaminski & Jaupart 2003;Bond & Johari 2005;Whittaker & Lister 2008;van Keken, Davaille & Vatteville 2013;Kondrashov, Sboev & Dunaev 2016a;Kondrashov, Sboev & Rybkin 2016b), the properties of thermal structures generated by a small heat source could be affected by several factors in laboratory experiments. These factors include mainly the dimensions and geometries of the heat source and the tank, the boundary conditions, the properties of the fluid, and the leakage of the heating power.…”
Section: Apparatus and Key Parametersmentioning
confidence: 99%
“…According to previous studies (Moses et al 1993;Kaminski & Jaupart 2003;Bond & Johari 2005;Whittaker & Lister 2008;van Keken, Davaille & Vatteville 2013;Kondrashov, Sboev & Dunaev 2016a;Kondrashov, Sboev & Rybkin 2016b), the properties of thermal structures generated by a small heat source could be affected by several factors in laboratory experiments. These factors include mainly the dimensions and geometries of the heat source and the tank, the boundary conditions, the properties of the fluid, and the leakage of the heating power.…”
Section: Apparatus and Key Parametersmentioning
confidence: 99%
“…Since the work of Batchelor (1954) and Morton, Taylor & Turner (1956) on the modelling of plumes, increasing attention has been devoted to the study of plumes. Starting plumes, which rise above a horizontal surface in a two-dimensional model (Hier et al 2004;Hattori et al 2013b;Van den Bremer & Hunt 2014), on a three-dimensional circular disk (Robinson & Liburdy 1987;Kitamura & Kimura 2008;Plourde et al 2008;Lesshafft 2015;Kondrashov, Sboev & Rybkin 2016b;Sboev, Rybkin & Goncharov 2018;Sboev & Kuchinskiy 2020), and from a line heat source (Noto 1989;Hattori et al 2013a), were studied using theoretical, experimental and numerical methods with a focus on the heat transfer and evolution of plume structures (e.g. cap and stem).…”
Section: Introductionmentioning
confidence: 99%
“…2013 b ; Van den Bremer & Hunt 2014), on a three-dimensional circular disk (Robinson & Liburdy 1987; Kitamura & Kimura 2008; Plourde et al. 2008; Lesshafft 2015; Kondrashov, Sboev & Rybkin 2016 b ; Sboev, Rybkin & Goncharov 2018; Sboev & Kuchinskiy 2020), and from a line heat source (Noto 1989; Hattori et al. 2013 a ), were studied using theoretical, experimental and numerical methods with a focus on the heat transfer and evolution of plume structures (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…When acceleration occurs, the detected temperatures change, but only by small amount. It has been found that the Zaxis detection accelerometer has a close relation with the natural convection of the flow inside a cavity heated from below [48][49][50][51][52][53]. In recent years, many researchers have found that boundary conditions [48,49] and heater geometry [50,51] have substantial impact on the pattern of these convective flows.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers have found that boundary conditions [48,49] and heater geometry [50,51] have substantial impact on the pattern of these convective flows. Because of the temperature distribution, the local heating of the quiescent air over the heater surface produces density gradient directed toward the decrease in the medium temperature, and convective flow occurs in the form of thermal plume when the buoyancy exceeds the viscous friction [53]. For a single local heater under heating conditions, the hot air rises upwards along the vertical axis going through the heater.…”
Section: Introductionmentioning
confidence: 99%